Transformasi Limbah Pertanian dan Rumah Tangga Menjadi Pupuk Organik: Upaya Pemberdayaan Masyarakat di Kelurahan Tuapukan, Kecamatan Kupang Timur - Bunyani, Nur Aini; Eka Citra Gayatri Kerihi; Nardi Matias Leo; Charisal Matsen Manu (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity was carried out by a team of lecturers from the 1945 Teachers' Union University (Universitas Persatuan Guru 1945) in East Nusa Tenggara in Merdeka Village, East Kupang District, with the aim of improving the community's knowledge and skills in processing organic waste into liquid and solid organic fertilizers. The background to this activity was based on the high volume of underutilized organic waste and the increasing community demand for organic fertilizers as an environmentally friendly and economical alternative. The implementation methods included observation, outreach, practical training, mentoring, and participatory evaluation. The results of the activity showed a significant increase in community understanding and skills related to organic waste management, the creation of solid and liquid organic fertilizer products, and the emergence of community initiatives to continue the activity independently. This activity also had a positive impact on environmental cleanliness and encouraged the development of new environmentally-based businesses. It was concluded that community-based waste management can be an effective solution in supporting sustainable agriculture and local economic empowerment. Future recommendations include the need for further mentoring, government support, the formation of local communities, and the integration of this program into food security strategies and further training.